Securing climate finance through national development banks - Stephany Griffith-Jones; Samantha Attridge; Matthew Gouett (Overseas Development Institute (ODI), 2020)
A key challenge in the collective endeavour to combat the climate emergency is the shift of global investment and financing flows that underpin current and future growth to low-carbon, climate-resilient (LCCR) growth. The global community recognises this challenge: it is one of the three long-term goals of the 2015 Paris Agreement of the United Nations Framework Convention on Climate Change (UNFCCC). National development banks (NDBs) and their governments are well placed to support this transformational change and the realignment of financial flows to ensure that they support the Paris goals. Further, it is very much in the interest of NDBs to understand and manage the financial risks to their investment portfolios from the transitional and physical risks of climate change. This study focuses on just one aspect of the transition: the need to invest in LCCR infrastructure to lock in LCCR growth trajectories and how NDBs can support this, through both direct financing and the mobilisation of private finance to fund the huge investment required.
Keywords: 330; Klimapolitik; Finanzierung; Entwicklungsbank; Treibhausgas-Emissionen; Welt